Ecopolis - Paul F Downton ; edited by Jack Ahern, John Bolte, Richard Dawson, Patrick Devine-Wright, Almo Farina, Ray Green, Glenn Guntenspergen, Dagmar Haase, Mike Jenks, Cecil Konijnendijk, Stephan Pauleit, Steward T. A. Pickett, Robert Vale, Ken Yeang, Makoto Yokohari. (Springer, 2017)
610 p.